PERAN KEPEMIMPINAN PENDIDIKAN DI YAYASAN MIMBAR HUFFAZH KARAWANG - Khusnul Fitriyana; Eriyatuzzahro; Irnie Victorynie (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study explores the function and role of school leadership in mobilizing institutional life and addressing organizational challenges at Mimbar Huffazh Foundation, Karawang. Using a qualitative descriptive method, data were collected through in-depth interviews and analyzed thematically. Findings reveal that the principal plays a strategic and dynamic leadership role, blending transformational and situational approaches that align with the unique cultural and professional context of the school. The leadership practice goes beyond administrative tasks by emphasizing vision-building, adaptive communication, and fostering professional growth. Open dialogue, relational trust, and participatory decision-making become central to how the principal navigates problems and drives continuous improvement. Moreover, teacher development programs are designed based on individual needs, reflecting a human-centered approach to school management. This study concludes that effective school leadership requires not only managerial competence but also the ability to inspire, adapt, and collaborate meaningfully. Future research is recommended to compare leadership practices across various Islamic educational institutions using mixed methods approaches for broader insight. Keywords: educational leadership, transformational leadership, situational leadership, communication strategy, education management